Output collapses and productivity destruction - Juan S. Blyde; Christian Daude; Eduardo Fernández-Arias (Inter-American Development Bank, Research Department, 2009)
This paper analyzes the long-run relationship between output collapses-defined defined as GDP falling substantially below trend - and total factor productivity (TFP), using a panel of 71 developed and developing countries during the period 1960-2003 to identify episodes of output collapse and estimate counterfactual post-collapse TFP trends. Collapses are concentrated in developing countries, especially African and Latin American, and were particularly widespread in the 1980s in Latin America. Overall, output collapses are systematically associated with long-lasting declines in TFP. The paper explores the conditions under which collapses are least or most damaging, as well as the type of shocks that make collapses more likely or severe, and additionally quantifies the welfare cost associated with output collapses.
Keywords: F43; O40; 330; Growth; recessions; productivity; recovery; Gesamtwirtschaftliche Produktion; Sozialprodukt; Produktivität; Wirtschaftswachstum; Wachstumszyklus; Welt